Model Matematika Populasi Plankton dan Konsentrasi Nitrogen - Elvi Silvia; Yarman Yarman; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2014)
Abstract – Phytoplankton and zooplankton have a major impact on the marine ecosystem because plankton is the main food chain in the ecosystem. However, this plankton’s concentration changes is influenced by nitrogen concentrations. This study began by making mathematical model based on the variables , parameters and assumptions that have been determined. Next step are finding and analyze an equilibrium point. Mathematical model in plankton populations and nitrogen concentration in the form of non-liner differential equation system. This dinamical system have two equilibrium points ie the points where nitrogen without plankton and the point where nitrogen and plankton. The stability of the system can be viewed from two condition, first when the system has one point where nitrogen without planktonthen this point will be stable. Second, when the system have two equilibrium points then only point where nitrogen and plankton will be stable. This result show that population of phytoplankton, zooplankton and nitrogen concentration will not disappear in the long term. Keywords – Nitrogen, plankton, mathematical model